2022
DOI: 10.1108/ajar-12-2021-0266
|View full text |Cite
|
Sign up to set email alerts
|

Product innovation, firm performance and moderating role of technology capabilities

Abstract: PurposeThis research aims to provide evidence that firms that create product innovations (PROINVs) can improve the performance of firms in Indonesia. And then this research also provides evidence that firms with high technological capabilities can moderate the impact of PROINV on firm performance in Indonesia.Design/methodology/approachBased on the firm that disclosure research and development expenditures, the number of samples in this study is 261 annual reports for the period 2015–2020. Researchers used an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 65 publications
(230 reference statements)
2
6
0
2
Order By: Relevance
“…It is shown that the industry, whether from the technology sector or consumer goods, cannot strengthen the relationship between profitability and sustainable growth rate. This is in line with research findings from Agustia et al, (2022) found that firms with high technological capabilities can weaken the impact of product innovation on firm performance, which will also certainly impact sustainable A company growth. This is because companies with high technological capabilities focus more on process or system innovation than product innovation.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It is shown that the industry, whether from the technology sector or consumer goods, cannot strengthen the relationship between profitability and sustainable growth rate. This is in line with research findings from Agustia et al, (2022) found that firms with high technological capabilities can weaken the impact of product innovation on firm performance, which will also certainly impact sustainable A company growth. This is because companies with high technological capabilities focus more on process or system innovation than product innovation.…”
Section: Discussionsupporting
confidence: 90%
“…Although the sixth hypothesis is rejected, it shows that the technology and consumer goods industries cannot strengthen the relationship between capital structure and sustainable growth rates. However, this research aligns with the findings of Agustia (2022), who found that capital/leverage structure does not interact with product innovation and technological capabilities in moderating the effect of product innovation on company performance. This may indicate that the moderating effect of technological capability is not influenced by capital structure/leverage but rather by the characteristics and quality of the technical capability itself.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Such value-added products result in changing their customer purchasing behaviour and further result in enhancement of their sale. In this context: the literature also proposed that the value-added products result in the betterment of the firm performance (in terms of sales) (Agustia, Haryanto, Permatasari, & Midiantari, 2022;Ramadani et al, 2019). Another factor that does impact here is the cultural capital or the team which work behind the innovation.…”
Section: Introductionmentioning
confidence: 99%